Qualitative analysis of anti-abortion discourse used in arguments for a 6-week abortion ban in South Carolina - Victoria C. Lambert; Emily E. Hackworth; Deborah L. Billings (Frontiers Media S.A., 2023)
BackgroundOn June 24, 2022, The U.S. Supreme Court overturned Roe v. Wade, leaving abortion legislation entirely up to states. However, anti-abortion activists and legislators have organized for decades to prevent abortion access through restrictive state-level legislation. In 2019, South Carolina legislators proposed a bill criminalizing abortion after 6 weeks gestation, before most people know they are pregnant. The current study examines the anti-abortion rhetoric used in legislative hearings for this extreme abortion restriction in South Carolina. By examining the arguments used by anti-abortion proponents, we aim to expose their misalignment with public opinion on abortion and demonstrate that their main arguments are not supported by and often are counter to medical and scientific evidence.MethodsWe qualitatively analyzed anti-abortion discourse used during legislative hearings of SC House Bill 3020, The South Carolina Fetal Heartbeat Protection from Abortion Act. Data came from publicly available videos of legislative hearings between March and November 2019, during which members of the public and legislators testified for and against the abortion ban. After the videos were transcribed, we thematically analyzed the testimonies using a priori and emergent coding.ResultsTestifiers (Anti-abortion proponents) defended the ban using scientific disinformation and by citing advances in science to redefine "life." A central argument was that a fetal "heartbeat" (i.e., cardiac activity) detected at 6 weeks gestation indicates life. Anti-abortion proponents used this to support their argument that the 6-week ban would "save lives." Other core strategies compared anti-abortion advocacy to civil rights legislation, vilified supporters and providers of abortion, and framed people who get abortions as victims. Personhood language was used across strategies and was particularly prominent in pseudo-scientific arguments.DiscussionAbortion restrictions are detrimental to the health and wellbeing of people with the potential to become pregnant and to those who are pregnant. Efforts to defeat abortion bans must be grounded in a critical and deep understanding of anti-abortion strategies and tactics. Our results reveal that anti-abortion discourse is extremely inaccurate and harmful. These findings can be useful in developing effective approaches to countering anti-abortion rhetoric.